Prostate-specific antigen testing for prostate cancer screening: A national survey of Canadian primary care physicians’ opinions and practices - Goldenberg, Mitchell Geoffrey (Can Urol Assoc J, 2017)
INTRODUCTION: In 2014, the Canadian Task Force on Preventive Health Care (CTFPHC) recommended against routine prostate cancer screening with the prostate-specific antigen (PSA) blood test.1 We surveyed Canadian primary care physicians (PCPs) to understand their opinions and attitudes towards prostate cancer screening in 2016. METHODS: Twenty PCPs piloted the survey to assess its accessibility. We distributed a flyer to 19 633 PCPs as an insert in a large mailed package inviting them to attend a national meeting, and later promoted the survey at the meeting. Multinomial logistic regression models examined factors associated with agreement of key guideline statements and the overall benefit of PSA screening. RESULTS: A total of 1254 PCPs responded (rate of 6.4%); 54.7% of physicians aware of the CTFPHC recommendations report screening less often as a result. Overall, 55.6% of PCPs feel that the risks of PSA screening outweigh the benefits. On multivariable analysis, physicians who did not read the guidelines, did not have an academic appointment, or were in practice for over 20 years were significantly more likely to disagree with the statement that men 55–69 years old should not be screened for prostate cancer with PSA. CONCLUSIONS: Our national survey found that the prostate cancer screening practices of Canadian PCPs varies widely across physician demographic groups, with almost equal numbers for or against. This has significant ethical, medical, and legal implications. The poor response rate to highly incentivized survey request may suggest a reluctance or general apathy towards this subject because of the Task Force recommendations. Future efforts should provide physicians with objective guidance around PSA screening, incorporating input from all stakeholders, including PCPs, urologists, and patients.